Daya Inhibisi Korosi Ekstrak Daun Belimbing Wuluh (Averrhoa bilimbi L.) terhadap Kawat Thermal NiTi Ortodonti (Corrosion Inhibition of Starfruit Leaves Extract (Averrhoa bilimbi L.) on Thermal NiTi Orthodontic Wire) - Irdian Devi Saputri; Rudy Joelijanto; Leliana Sandra Devi Ade Putri Putri (Pustaka Kesehatan, 2015)
Orthodontic wire can corrode in oral cavity. Corrosion can affect human body and feature of orthodontic wire. One way to reduce corrosion rate is using inhibitor. Natural ingredients extract inhibitor is usually preferred because it’s not harmful to environment. One of natural ingredients that can be used is starfruit leaves. This study was aimed to determine the corrosion inhibition of starfruit leaves extract on Thermal NiTi orthodontic wire. This study was an experimental laboratory research. Samples was 12 Thermal NiTi orthodontic wire which had been prepared and then divided into control group, 600 ppm group and 1000 ppm group. Then samples were measured by using a potentiostat. Results of Kruskal Wallis test and Mann-Whitney test showed a significant difference between groups. The conclusion from this research was there were starfruit leaves extract have corrosion inhibition on thermal NiTi orthodontic wire. Keyword: corrosion inhibiton, starfruit leaf extract, thermal NiTi orthodontic wire